GREEN SYNTHESIS OF SILVER NANOPARTICLES FROM THE LEAF EXTRACT OF ADHATODA VASICA NEES. AND ASSESSMENT OF ITS ANTIBACTERIAL ACTIVITY - Bhumi G; Linga Rao M; Savithramma N (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Introduction: Green synthesis of nanoparticles has been an exploring research topic in recent days due to their advanced uses in biomedical, chemical, and related fields. Objective: The objective of the present study was to rapidly synthesize silver nanoparticles (AgNPs) using Adhatoda vasica leaf extract. The nanoparticles obtained have been characterized with various techniques like ultraviolet-visible spectrum, Fourier transform (FT) infrared spectrometry, scanning electron microscopy, energy dispersive spectroscopy, X-ray diffraction, atomic force microscopy, and FT-Raman spectroscopy. Results: These techniques showed the formation of AgNPs with an average size of 21.1-29.1 nm. Phytochemicals present in the plant were responsible for the quick reduction of Ag+ ions to Ag0 nanoparticles. The synthesized AgNPs had the potential to mitigate the bacterial and fungal cell proliferation particularly Staphylococcus aureus, Pseudomonas auroginosa, Bacillus thuringiensis, Escherichia coli, Klebsiella pneumoniae and fungal species were Aspergillus niger, Aspergillus flavous, Pencillium chrysogenum, and Trichoderm harizanum. The results were compared with ciprofloxacin and fluconazole as positive controls. Conclusion: A. vasica being a crucial medicinal plant widely used in the treatment of cancer, the present study shows that the plant can be used as best source for synthesis of AgNPs for further research in the cancer field. Keywords: Adhatoda vasica, Phytochemials, Phenols, Fourier transform Raman spectroscopy, Atomic force microscopy.